Android Based Motorcycle Sales information System Design - Mochamad Hidayatullah (Universitas Muhammadiyah Sidoarjo, 2022)
CV. Jaya Motor is one of the companies engaged in the sale of Honda motorcycles in the city of Sidoarjo in developing sales and promotions at this time CV. Jaya Motor still uses the sales system by distributing brochures even though it has been going well in the city of Sidoarjo but this is not optimal for today because not all people can receive information about CV. Jaya Motor obviously this greatly affects the sales of the Dealers products. Android-based sales information system by utilizing the internet as a means to market products with the hope of CV. Jaya Motor is better known and its products are more in demand by the people of Sidoarjo in particular and by internet users in general. Motorcycle sales information system that is displayed is the sale of motorcycles with a telephone system to marketing with media information via android.